1999
DOI: 10.1042/cs0960049
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic nervous system dysfunction in sclerodermic and primary Raynaud's phenomenon

Abstract: Our aim was to investigate the sympathetic hyperactivity of systemic sclerosis that may lead to greater morbidity and mortality from cardiovascular events. We analysed the sympathetic (low-frequency) and vagal (high-frequency) components of heart rate variability, in supine and upright positions, in 10 patients with systemic sclerosis, 12 patients with primary Raynaud's phenomenon and 14 controls. We also analysed lung function in order to evaluate a possible link between heart rate variability and ventilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
1
12
1
2
Order By: Relevance
“…In addition, Pancera et al40 found that HRV was reduced in patients with SSc in comparison to control subjects. On the contrary, Morelli et al41 analyzed HRV in the time domain and showed no significant difference in any variable between SSc patients and the controls.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, Pancera et al40 found that HRV was reduced in patients with SSc in comparison to control subjects. On the contrary, Morelli et al41 analyzed HRV in the time domain and showed no significant difference in any variable between SSc patients and the controls.…”
Section: Discussionmentioning
confidence: 97%
“…Both sympathetic and parasympathetic dysfunction have been observed. 26 HR variability is reduced and sympathetic output increased in patients with SSc, 27 so a MIBG abnormality and rapid MIBG turnover may reflect sympathetic derangement in SSc. Gürtner et al reported that 123 I MIBG scintigraphy revealed an inhomogeneous reduction in 15 patients (83%).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the presence of cardiac autonomic dysfunction in Sjögren's syndrome patients, particularly in those with anti-Ro/SSA autoantibodies (6). Autonomic dysfunction has also been observed in other anti-Ro/SSA-positive connective tissue diseases, such as systemic lupus erythematosus and systemic sclerosis (7,8). These observations suggest that anti-Ro/SSA autoantibodies may determine a dysfunction in cardiac autonomic activity.…”
mentioning
confidence: 96%